Design and Simulation for Technological Integration of Bio-Based Components in Façade System Modules - Alessandro Pracucci; Laura Vandi; Luca Morganti; Ana Gallego Fernández; Miguel Nunez Diaz; Arsenio Navarro Muedra; Viktor Győri; Jean-Luc Kouyoumji; Julen Astudillo Larraz (Buildings, 2024)
Driven by environmental sustainability concerns, the integration of bio-based components in curtain wall systems is gaining traction in both research and the construction market. This paper explores the development and validation of a bio-based façade system within the Basajaun H2020 project (2019–2024). The project aimed to demonstrate the feasibility of introducing environmentally friendly bio-based components into the mature curtain wall façade industry. The paper focuses on identifying technological solutions for replacing key components such as frame profiles, insulation, and the tightness system with bio-based and less environmentally impactful alternatives, presenting the results achieved in the façade system design of the Basajaun project. These solutions aimed at creating a bio-composite-based curtain wall façade that adheres to the current building envelope standards and normative, implementing diverse façade typologies for vision panels, opaque sections, and integrated windows and, moreover, engineering the prefabrication process for industrialization and enabling wider market replication and simplified transport and installation. The results demonstrate that the Basajaun façade successfully integrates selected components and meets the performance requirements set by regulations: the façade is designed to withstand a maximum and typical wind load of 3.5 kN/m2 and a typical load of 1.5 kN/m2, the weighted sound reduction index obtained is Rw = 44 dB, and the thermal transmittance of the vision façade is 0.74 W/m2K while that of the entire opaque façade is 0.27 W/m2K (an additional internal wall is required to achieve the requested thermal transmittance)—the values are in accordance with reference standards and design requirements. However, questions remain regarding the workability of bio-based profiles as a commercially viable, ready-to-market solution that can replace traditional aluminum profiles in the curtain wall façade industry.